Pengaruh Kepuasan Kerja Dan Komitmen Organisasional Terhadap Turnover Intention,Effect of Job Satisfaction and Organizational Commitment on Turnover Intention. - Perpustakaan UGM, i-lib ([Yogyakarta] : Sekolah Pascasarjana Universitas Gadjah Mada, 2003)
ABSTRACTThis study examines three turnover intention models that are developed from studies by Clugston (2000) and Herndon et al. (2001). The three models are tested with structural equation modeling. Each model includes job satisfaction, and organizational commitment (affective, continuance, and normative) factors which affect turnover intention. The best model of the study suggests that job satisfaction affects turnover intention which in turn is partially mediated by three dimensional organizational commitments. One hundred and fifteen auditors from "the big five" public accountant firms were the respondents in this research.